Modeling the Impact of TikTok-Based Digital Marketing on Fashion Purchase Intention among Indonesian Millennials: A PLS-SEM Approach - Rizal, Rizal Ramdani; Susilo, Susilo Talidobel; Rahmatullah, Arwin Yafi; Assa’ady, Muhammad Chothibul Umam (Lentera Ilmu Nusantara, 2025)
The digital era has transformed the fashion marketing paradigm with the emergence of TikTok as a communication medium targeting the millennial generation. This study aims to analyze the influence of TikTok digital marketing on the purchase intention of fashion products among Indonesian millennials.A quantitative approach was employed using an explanatory research design through a survey of 200 millennial respondents active on TikTok. The data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS to examine the relationships between the variables of Perceived Quality, Brand Attitude, Electronic Word of Mouth (E-WOM), and Purchase Intention. Thus, the results of the study indicate that all hypotheses are statistically supportedon Purchase Intention. Perceived Quality had the strongest influence on Purchase Intention, followed by Brand Attitude and E-WOM on Purchase Intention. Therefore, the study contributes theoretically to the digital marketing literature and offers practical insights for fashion brands in optimizing their TikTok marketing strategies. Managerial implications highlight the importance of focusing on visual content quality, building a positive brand attitude, and implementing community engagement strategies to drive organic E-WOM within the TikTok digital marketing ecosystem.